Comparative Study of Ethanolic and n-Hexane Extracts of Cassia angustifolia as Anticancer Agents against Human Cancer Line MDA-MB-231 (Journal of Agriculture and Biology, 2025)
Cancer is characterized by the uncontrolled and undifferentiated proliferation of cells, with the potential to invade and metastasize to various parts of the body. The use of conventional herbal extracts represents a promising approach in the search for novel anticancer agents due to the presence of bioactive phytochemicals in medicinal plants. In this study, the anticancer activity of ethanolic and n-hexane extracts of Cassia angustifolia was evaluated against the human breast cancer cell line MDA-MB-231. Five different concentrations (0, 50, 100, 250 and 500 µl/ml) of each extract were tested to determine the optimal cytotoxic dose. At 250 µl/ml of the ethanolic extract, most cells appeared rounded and detached from the surface, while the remaining cells were elongated and loosely adhered. At the highest dose of 500 µl/ml, extensive cell death was observed, with cellular debris indicating significant cytotoxicity. In contrast, the n-hexane extract at 50 µl/ml showed negligible changes in cell morphology compared to the control. However, increasing concentrations led to reduced cell viability. The half-maximal inhibitory concentration (IC₅₀) was determined to be 83 for the ethanolic extract and 283 for the n-hexane extract. These findings suggest that the ethanolic extract of Cassia angustifolia exhibits greater anticancer efficacy against the MDA-MB-231 cell line compared to the n-hexane extract, likely due to the differential solubility and availability of bioactive compounds in the two solvents.